Accounting for intangible assets – insights from meta-analysis of R&D research. Issue 1 (8th December 2021) - Jeny, Anne; Moldovan, Rucsandra
Abstract : Purpose: The knowledge- and Internet-based economy demands a reexamination of the accounting treatment for intangibles and a thorough understanding of the empirical evidence on this topic. Design/methodology/approach: The study reviews the literature on research and development (R&D), a specific internally developed intangible asset, using meta-analysis techniques that allow to highlight the areas of consensus and disagreement in quantitative empirical results. The literature the authors review addresses four main research questions on (1) the determinants of the decision to capitalize R&D, (2) stock market-based outcomes of capitalizing R&D, (3) firm-based outcomes related to expensing R&D and (4) stock market-based outcomes of expensing R&D. Findings: The authors find higher value relevance of capitalized compared with expensed R&D. There is, however, little robust evidence on the determinants of the capitalization decision and the characteristics of capitalizers. Originality/value: The authors conclude by highlighting future research that can allow accounting academics to contribute to standard setting.